2020
DOI: 10.1080/11263504.2020.1727976
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological and anatomical characteristics of Salvia amplexicaulis Lam., S. jurisicii Košanin and S. ringens Sibth. & Sm. (Lamiaceae)

Abstract: In this study, we examined Salvia amplexicaulis Lam., S. jurisicii Košanin and S. ringens Sibth. & Sm.collected in the Republic of North Macedonia, which are for the first time subjected to detailed micromorphological and structural analysis using light and scanning electron microscopy. The nutlets and mucilage were additionally subjected to spectroscopic analysis using Raman and Attenuated Total Reflectance Fourier Transform Infrared (ATR FT-IR) spectroscopy. The anatomical structure of stems and leaves is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
(154 reference statements)
1
0
0
Order By: Relevance
“…The primary vein category is pinnate. This result is in agree with (Alimpić Aradski et al, 2021) indicated that primary vein of some species of Salvia is pinnate.…”
Section: Discussionsupporting
confidence: 93%
“…The primary vein category is pinnate. This result is in agree with (Alimpić Aradski et al, 2021) indicated that primary vein of some species of Salvia is pinnate.…”
Section: Discussionsupporting
confidence: 93%